Reviews and Prospects of Contemporary Chinese Religious Study - LI, Jianxin (Journal of Research for Christianity in China (JRCC), 2025)
This paper first adopts the seven-dimensional framework proposed by the famous American scholar of religious studies Ninian Smart to reveal that religion, the object of religious studies, is a complex and multifaceted socio-historical phenomenon. The second part reviews the development of religious studies in China since the Republic of China until the reform and opening up: (1) the foundation of modern Chinese religious studies: 1920s and 1930s; (2) the beginning of contemporary Chinese religious studies: 1949-1966; (3) the waning period of contemporary Chinese religious studies: 1966-1978. The third part describes the development of Chinese religious studies in the 40 years since the reform and opening up in two parts: (1) the restoration and reconstruction of contemporary Chinese religious studies: 1978-1990s; and (2) Chinese religious studies in the new era. Finally, it presents a preliminary vision of the construction of the disciplinary system of religious studies in China.
Keywords: Contemporary Religious Studies, Review, Outlook